2014
DOI: 10.1302/0301-620x.96b1.32581
|View full text |Cite
|
Sign up to set email alerts
|

The surgical management of spinal deformity in children with a Fontan circulation

Abstract: The management of spinal deformity in children with univentricular cardiac pathology poses significant challenges to the surgical and anaesthetic teams. To date, only posterior instrumented fusion techniques have been used in these children and these are associated with a high rate of complications. We reviewed our experience of both growing rod instrumentation and posterior instrumented fusion in children with a univentricular circulation. Six children underwent spinal corrective surgery, two with cavopulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Evans et al also suggested that patients with Fontan circulation have high venous pressure, particularly while in the prone position. Hence, operations requiring the prone position in these patients may result in significant blood loss [10]. Considering these concerns, we took extra care during the operation to avoid excessive blood loss in case 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evans et al also suggested that patients with Fontan circulation have high venous pressure, particularly while in the prone position. Hence, operations requiring the prone position in these patients may result in significant blood loss [10]. Considering these concerns, we took extra care during the operation to avoid excessive blood loss in case 1.…”
Section: Discussionmentioning
confidence: 99%
“…Hypotensive anesthesia is often useful to prevent bleeding, although CHD patients with unstable hemodynamics can easily develop hypoperfusion. Evans et al reported that operations during which the patient must remain prone for more than 4 h were associated with an increased risk of bleeding and hypotension, even when the patient was initially hemodynamically stable [10]. Patients with Fontan circulation (as in case 1) receive lifelong anticoagulant therapy, which makes the perioperative use of hemostatic agents difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal surgery in patients with CHD has become safer with time, however the risk of perioperative complications remains high 17–21 . This risk is greatest in patients with single ventricle physiology and requires multidisciplinary care and preparation for adverse perioperative events 21–27 . Our institution recently reviewed 78 patients with CHD undergoing scoliosis surgery and found patients with cyanotic single ventricle physiology had the highest risk for adverse perioperative events 21 .…”
mentioning
confidence: 99%
“…[17][18][19][20][21] This risk is greatest in patients with single ventricle physiology and requires multidisciplinary care and preparation for adverse perioperative events. [21][22][23][24][25][26][27] Our institution recently reviewed 78 patients with CHD undergoing scoliosis surgery and found patients with cyanotic single ventricle physiology had the highest risk for adverse perioperative events. 21 Our single ventricle physiology cohort has grown since this research and an earlier review of Fontan patients.…”
mentioning
confidence: 99%